Calculations and Distribution of Shares in The Islamic System of Inheritance: A Beginner Approach - Wakili, A.A.; Yusha’u, Abubakar Sabo; Yahya, Ahmad (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This paper attempts to present a learner friendly formula for calculation and distribution of heirs. The aim is to acquaint teachers, students, emerging judges and lawyers, as well as, other legal practitioners with an easier and simpler formular inorder to allay fears and difficulties with which other formulae are mostly identified. The research method used in this article is descriptive, with the main approach based on document or context analysis. The author bases his study on primary sources relevant to the science of Mirath (Islamic inheritance system), both in print, electronic, and online forms.This research is to simplify the process of calculating and distributing inheritance in the Islamic inheritance system through a more learner-friendly approach. The proposed new approach shows that by mastering basic principles such as derackionalization and fractional denomination management, inheritance distribution can become simpler and more accurate. These findings not only help teachers and students of Islamic religious sciences, but also practitioners of sharia law to avoid mistakes and strengthen social justice according to Islamic principles.